A corpus-based study on the use of preposition in Malaysian secondary school English language textbooks - Roslim @ Roslind, Norwati (2013)
Malaysian learners are observed to have some difficulties in the use of English prepositions. This study, thus, investigated the presentation of English prepositions in the KBSM syllabus (Ministry of Education, 2003) and the Malaysian Secondary School English language textbook corpus of Forms 1 to 5 (Mukundan & Anealka, 2007). The aims of the study were to investigate: (1) the list of prepositions outlined in the KBSM syllabus and compared to the British National Corpus (BNC), (2) the descriptions of prepositions offered by the linguists and grammarians and compared to the descriptions of prepositions in the KBSM syllabus and the Malaysian Secondary School English language textbooks, (3) the distribution patterns of prepositions in Malaysian Secondary School English language textbooks, (4) the ways in which the teaching of prepositions were presented in the Malaysian Secondary School English language textbooks. These were addressed in five research questions and the research design comprised a qualitative content analysis. The research findings of this study have shown several valuable insights. Firstly, the findings showed that there were words which were categorized as prepositions in the syllabus did not appear in the list of prepositions in the BNC such as ‘so that’ and ‘in order to’. This study also revealed that the order for certain prepositions outlined in the syllabus did not quite agree with the frequency list found in the BNC. Additionally, this study discovered that not all the prepositions stipulated in the syllabus were presented in the Malaysian Secondary School English language textbooks of Forms 1 – 5. Secondly, it was found that the descriptions of prepositions in the syllabus and textbooks were very limited. Thirdly, the distribution patterns of prepositions in the Malaysian Secondary English language textbooks showed that there were prepositions being presented less than seven times within and across the textbooks. Fourthly, the presentation of the teaching of prepositions in the Malaysian Secondary English language textbooks focused more on the semantic functions of prepositions and minimal attention was given to the collocations of prepositions and forms or the phrase structure of prepositions. Some prepositions were not mentioned in any way and when prepositions were presented in the textbooks, they were usually given a page or less and they were not actually explained in any detail. Finally, the types of tasks presented in the Malaysian Secondary English language textbooks of Forms 1 – 5 lacked variations and they were unevenly distributed. It was concluded that there were some inadequacies in the syllabus as well as the Malaysian Secondary English language textbooks of Forms 1 – 5 and the inadequacies found could have led to the problems encountered by the ESL students in using English prepositions. In order to tackle the inadequacies found in the syllabus and the Malaysian Secondary English language textbooks of Forms 1 – 5 and to further improve the teaching and learning of prepositions among ESL learners, several recommendations were proposed. These include reviewing the syllabus and the contents of textbooks and incorporating some pedagogical aspects that would help teachers and learners in the teaching and learning of English prepositions.